A cross sectional study to assess the effects of excessive use of smartphones among professional college going students - Rai, Shailesh; Saroshe, Satish; Khatri, A. K.; Sirohi, Suraj; Dixit, Sanjay (International Journal Of Community Medicine And Public Health, 2017)
Background: Smart phones have now become an essential part of life. However, despite the convenience it brings to use, sometimes it might affect our daily life in a negative sense. The objective of the study was to explore the pattern of mobile phone usage among professional college going students in Indore, India also to examine the extent of addictive behaviour towards the usage of mobile phones. Methods:A total of 300 students of different streams having smartphones were surveyed regarding the usage of smartphone considered as population and simple random sampling technique was used. A well-structured and administered questionnaire was used to elicit the responses. The collected data were analysed with the help of various tools and techniques to draw meaningful inferences and conclusion which were obtained using Excel and some using SPSS. The study was conducted during September 2014 to December 2014. Results: In present study maximum number of the students used smartphone around 4 hours daily and mostly the use was for communication & social networking. Majority of students used their smartphone at home, thought that they used smartphone more than expectation, felt uncomfortable without their smart phone, got irritated by frequent notifications of smart phone and got angry when someone interrupts them while using smart phone. Conclusions:Most of the students felt that over uses of smartphones make their lives more sedentary, dry eyes and headache, feel disturbances in their sleep. Also, they spend excess money on mobile recharges although they prefer to use internet over their own creativity for any project.